Prototype Aplikasi Pembelajaran Daring Di Masa Pandemi Covid-19 Berbasis Cloud Storage - Siti Husnul Bariyah; Kuntum An Nisa Imania; Yuniar Purwanti (JURNAL PETIK, 2020)
Abstract - The Covid-19 pandemic that has been running for several months from April 2020 to September 2020 has caused adjustments in various fields, one of which is the field of education. Based on Circular No. 4 of 2020 concerning the implementation of education in the Covid-19 emergency period, one of the points is that the learning process is carried out from home, thus requiring the school to make a new innovation for the learning process because it does not allow face-to-face classrooms. The school and teachers make an agreement on how the method they will use. This research takes the example of a case in a private school in Bandung regency that implements online learning media through group wa found some of the deficiencies are for teachers there is no neat learning history because of its nature that continues to accumulate when there is an incoming message, for parents there is limited storage memory. which causes many obstacles in accessing the WA group to download teaching materials from the teacher or sending reports on the results of daily learning. Therefore researchers intend to develop a cloud storage-based online learning application prototype by utilizing a variety of technologies including Laravel programming language, react native (mobile ), Firebase for the use of its database and the Google Drive API for file cloud storage. The result of developing this prototype is in the form of a system design consisting of activity diagrams, use case diagrams, class diagrams and mobile-based interface designKeywords — Application, learning, online, cloud, storage Abstrak — Pandemic covid-19 yang telah berjalan beberapa bulan terhitung dari April 2020 sampai sekarang September 2020 telah menyebabkan penyesuaian di berbagai macam bidang salah satu diantaranya adalah bidang Pendidikan. Berdasarkan Surat Edaran No 4 Tahun 2020 tentang pelaksanaan Pendidikan dalam masa darurat covid-19, salah satu point nya adalah proses belajar dilaksanakan dari rumah, sehingga menuntut pihak sekolah untuk membuat sebuah inovasi baru untuk proses pembelajaran karena tidak memungkinkan untuk adanya tatap muka dikelas. Pihak sekolah dan guru membuat sebuah kesepakatan bersama bagaimana metode yang akan mereka gunakan. Penelitian ini mengambil contoh kasus di sebuah sekolah swasta di kab bandung yang menerapkan media pembelajaran daring memalui wa grup ditemukan beberapa kekurangan diantaranya adalah bagi guru tidak adanya histori pembelajaran yang rapih karena sifatnya yang terus menumpuk ketika ada pesan masuk, bagi orang tua adanya keterbatasan memori penyimpanan yang menyebabkan banyak kendala dalam mengakses WA grup untuk mengunduh bahan ajar dari guru atau mengirimkan laporan hasil pembelajaran harian.Oleh karena itu peneliti bermaksud untuk mengembangkan sebuah prototype aplikasi pembelajaran daring berbasis cloud storage dengan memanfaatkan berbagai macam teknologi diantaranya Bahasa pemrograman Laravel, react native (mobile), firebase untuk penggunaan database nya dan google drive API untuk file cloud storage. Hasil dari pengembangan prototype ini adalah berupa perancangan system yang terdiri dari activity diagram, use case diagram, class diagram dan desain antarmuka berbasis mobile.Kata Kunci— aplikasi,  pembelajaran, daring, cloud, strorage